Causal relationship between income inequality and economic growth in Ethiopia - Mihret Wolde; Leta Sera; Tesfaye Melaku Merra (Cogent Economics & Finance, 2022)
The aim of this study was to see the direction of causality and to investigate the existence of a long-run relationship between income inequality and economic growth in Ethiopia. The study has employed annual time series data over the period of 1980 up to 2017. This study is conducted by utilizing the Autoregressive Distributive Lag (ARDL) techniques. The ARDL bounds testing approach has been used for cointegration and the error correction method (ECM). The unit root problem is tested by the use of the ADF unit root test and the Phillips-Perron test. The researcher concluded that there is a negative relationship between income inequality and economic growth in the long run. However, in the short run, there is a positive relationship. The magnitude of the ETC coefficient is -1.004961 justified about 100.4961 percent, and the disequilibrium annually converges towards long-run equilibrium. In addition, VECM granger causality tests show that unidirectional causality runs from economic growth to income inequality both in the short and long run. The government should focus their efforts on the middle and poorest classes to reduce inequality and support sustainable economic growth of Ethiopia.
Keywords: 330; ARDL bound test; Economic growth; Income inequality and VECM